Pregnancy and Zika virus - T. V. Startseva; N. N. Kanshina; M. V. Tretyakova; V. O. Bitsadze; J. Kh. Khizroeva; L. S. Radetskaya; N. S. Stuleva; V. I. Tsibizova; A. S. Shkoda; D. V. Blinov; A. D. Makatsariya (Акушерство, гинекология и репродукция)
Zika virus (ZIKV) is an arthropod-borne virus (arbovirus) in the genus Flavivirus and the Flaviviridae family. In 1947 and 1948 ZIKV was first isolated from a nonhuman primate as well as from mosquitoes in Africa, respectively. For half a century, ZIKV infections in human were sporadic prior to 2015–2016 pandemic spreading. Transmission of ZIKV from mother to fetus can occur in any trimester of pregnancy, even if mother was an asymptomatic carrier. The clinical signs of ZIKV infection are nonspecific and can be misdiagnosed as some other infectious diseases, especially those caused by arboviruses such as Dengue and Chikungunya. ZIKV infection was solely associated with mild illness prior to the large French Polynesian and Brazil outbreaks, when severe neurological complications, Guillain–Barre syndrome and dramatically increased rate of severe congenital malformations (including microcephaly) were reported. The adaptation of ZIKV to an urban cycle in endemic areas suggests that the incidence of ZIKV infections may be underestimated. The pandemic of novel coronavirus infection (COVID-19) demonstrates that lessons from ZIKV pandemic propagation has not been learned properly.